External workload compared between competitive and non-competitive matches for professional male soccer players - Asian-Clemente, J.; Requena, B.; Owen, A.; Santalla, A. (Journal of Human Kinetics, 2022)
The purpose of this study was to compare the external load in competitive (official) and non-competitive matches (friendly, training and modified-sided games) in professional soccer players. Time-motion data for 10 elite male soccer players (age = 20.1 ± 2.1 years; body height = 178.8 ± 5.9; body mass = 71.4 ± 7.3; % body fat = 11.0 ± 1.1 and VO 2max = 55.96 ± 3.3) from a professional Spanish first division team were recorded during official (n = 12), friendly (n = 7) and training (n = 6) matches and a 5 vs. 5 + goalkeepers modified-sided game (n = 3). GPS devices were used to monitor players` external loads: total distance covered, distance covered at different speeds (<13.9 km·h-1, >14, >18, >21 and >25 km·h -1), peak speed (km·h -1), and the number of accelerations and decelerations (1.5-2.5 m·s -2, 2.5-4 m·s -2 and 4-8 m·s-2). One-way analysis of variance of the magnitude-based inference was used to determine differences between matches. Data indicated that official matches scored statistically higher peak speeds (ES = 1.40-2.20). In modified-sided games more total distance was covered at <13.9 km·h -1 and >14 km·h -1 than in regular matches (ES = 0.72-2.21), but lower distances were covered at >21 km·h -1 and >25 km·h -1 than in official and friendly matches (ES = 0.51-2.53) and at >25 km·h -1 than in training matches (ES = 0.92). Likewise, the modified-side games showed a greater number of accelerations and decelerations than other types of matches (ES = 1.46-2.51). This work shows that friendly and training matches, in conjunction with modified-side games, are suitable tools to prepare soccer players for official matches.